2019
DOI: 10.1080/13607863.2019.1647136
|View full text |Cite
|
Sign up to set email alerts
|

Employment adjustment and mental health of employed family caregivers in Canada

Abstract: In Canada, with the population aging, the need of family caregiving to older adults is increasing. Family caregivers make employment adjustment in order to fulfill caregiving responsibility. However, the studies on the family caregivers' mental health outcomes associated with employment adjustment are limited. Based on the role theory and stress process model, the current study examined the relationship between employment adjustment and mental health outcomes among family caregivers, and also tested the functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 192 publications
1
14
0
2
Order By: Relevance
“…In addition, nancial compensation from social support services, communities of faith and other family members was a helpful factor for them. In previous studies, family caregivers underwent negative psychological experiences, such as worsening mental health and increasing life stress levels, due to job instability including unemployment and turnover [35]. Therefore, the results of this study implies methods of reducing their burden of care, which is interpreted as having an important meaning in the resilience of family caregivers of dementia patients Moreover, this supports the previous research that growth and development are the main attributes of resilience [30,31].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, nancial compensation from social support services, communities of faith and other family members was a helpful factor for them. In previous studies, family caregivers underwent negative psychological experiences, such as worsening mental health and increasing life stress levels, due to job instability including unemployment and turnover [35]. Therefore, the results of this study implies methods of reducing their burden of care, which is interpreted as having an important meaning in the resilience of family caregivers of dementia patients Moreover, this supports the previous research that growth and development are the main attributes of resilience [30,31].…”
Section: Discussionsupporting
confidence: 84%
“…In addition, family caregivers providing care to aging parents tend to experience worse mental health than those supporting other family members or non-kin others. The association between the caregiver-receiver relation and mental health outcomes has been addressed in detail in previous studies (Li & Lee, 2019;Penning and Wu, 2016). The participants in this study are mainly middle-aged individuals, and their care receivers are usually aging parents at this lifecourse stage (Silverstein et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected consequences of employment adjustment include an increase in role conflict between work and family, particularly the family-to-work role conflict. Li & Lee ( 2019 ) have reported that employment adjustment is associated with worse mental health outcomes among family caregivers; its adverse impact on mental health results from an increased feeling of family-to-work role conflict due to employment adjustment. Another longitudinal study ( Hammer et al, 2005 ) identified similar findings among female caregivers only; Hammer et al (2005) suggested that in a gendered society, women are expected to be the family caregivers, and such expectations may increase if women make changes in their jobs to allow for caregiving responsibility.…”
Section: Introductionmentioning
confidence: 99%
“…Less is known about the influence of the multiple roles over time among individuals with different health conditions. One major reason is that health is usually examined as the outcome of holding several social and familial roles simultaneously, rather than a moderating effect (Barnett et al, 2012;Kohl et al, 2018;Li & Lee, 2020).…”
Section: Multiple Roles and Social Isolation Among The Middle-aged Generationmentioning
confidence: 99%